The Impact of Silver Nanoparticles Functionalized with Spirulina Protein Extract on Rats - Ludmila Rudi; Inga Zinicovscaia; Liliana Cepoi; Tatiana Chiriac; Dmitrii Grozdov; Alexandra Kravtsova (MDPI AG, 2024)
Background/Objectives: This study investigates the biocompatibility and physiological impacts of silver nanoparticles (AgNPs) functionalized with Spirulina protein extract (SPE) on laboratory rats. The objective was to assess and compare the systemic distribution, organ accumulation, and changes in hematological and biochemical parameters between biofunctionalized and non-functionalized silver nanoparticles. Methods: AgNPs were functionalized with SPE. Adult Wistar rats were administered these nanoparticles to assess their distribution across various organs using ICP-MS analysis. Hematological and biochemical markers were measured to evaluate systemic effects. Results: Functionalized silver nanoparticles demonstrated preferential accumulation in the brain, liver, and testicles, with significant clearance observed post-administration. The persistence of AgNPs SPE in reproductive organs was established. Hematological analysis revealed moderate changes, suggesting mild immune activation. Biochemical tests indicated transient increases in liver enzymes, signaling reversible hepatic stress. Conclusions: The biofunctionalization of AgNPs with Spirulina protein extract modifies the nanoparticles' systemic behavior and organ distribution, enhancing their biocompatibility while inducing minimal physiological stress. These findings support the potential of Spirulina-based coatings to mitigate the toxicity and enhance the therapeutic efficacy of nanomedical agents.